2018
DOI: 10.1037/xhp0000507
|View full text |Cite
|
Sign up to set email alerts
|

Parallel regulation of past, present, and future actions during sequencing.

Abstract: Past, present, and future actions must be regulated online to produce sequences of actions, but the regulation process is not well understood because of measurement limitations. We provide the first direct tests of the parallel action regulation hypothesis during sequencing in humans. We used transcranial magnetic stimulation to probe the level of excitation for flexion of the right index finger during typing. Motor evoked potentials (MEPs) were recorded at the onset of typing 5-letter words and nonwords. A si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Here the neural activation pattern for each sequence segment is weighted according to its temporal position in the sequence [6,7]. A rich literature indirectly supporting CQ in sequence control stems from observations of serial recall including transposition of neighbouring items and items occupying the same position in different chunks [6,8,9], and excitability of forthcoming items during sequence production [10]. Moreover, the CQ account has also been substantiated directly at the neurophysiological level in the context of well-trained finger sequences [11,12], saccades [13] and drawing geometrical shapes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Here the neural activation pattern for each sequence segment is weighted according to its temporal position in the sequence [6,7]. A rich literature indirectly supporting CQ in sequence control stems from observations of serial recall including transposition of neighbouring items and items occupying the same position in different chunks [6,8,9], and excitability of forthcoming items during sequence production [10]. Moreover, the CQ account has also been substantiated directly at the neurophysiological level in the context of well-trained finger sequences [11,12], saccades [13] and drawing geometrical shapes [14].…”
Section: Introductionmentioning
confidence: 99%
“…This pattern is clearly inconsistent with a serial model that does not predict an effect on execution. Previous electrophysiological studies, taking advantage of motor evoked potentials, showed that, at the onset of typing, motor information on hand alternation is detected only for the first part of the string (Behmer et al, 2018; Scaltritti et al, 2018). In line with serial models, Behmer et al (2018) proposed that all keystroke identities are processed and activated in parallel before typing execution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous electrophysiological studies, taking advantage of motor evoked potentials, showed that, at the onset of typing, motor information on hand alternation is detected only for the first part of the string (Behmer et al, 2018; Scaltritti et al, 2018). In line with serial models, Behmer et al (2018) proposed that all keystroke identities are processed and activated in parallel before typing execution. Later, during execution, the actual keystrokes inhibited the following ones according to a graduated activation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental evidence suggested that decision making arises from a continuous flow of information from the perceptual system to the motor system, leading to the build-up of evidence for one alternative along the system (e.g., Donner et al 2009), which makes it plausible to find response competition up to the motor system (Calderon, Gevers, & Verguts, 2018). Previous studies have described inhibition at the level of an effector, using TMS (Burle et al 2002;Duque et al 2010;; for typing see Behmer et al 2018). Interestingly, inhibition seemed restricted to relevant effectors, i.e., those involved in the block/task (Labruna et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the neurophysiological signature associated with response selection is modulated by item position within the upcoming sequence (close vs. distant). Consistently, Behmer et al (2018) used trans-cranial magnetic stimulation (TMS) to show a gradient of activation of motor cortex that corresponded to the graded position of future keystrokes.…”
Section: Introductionmentioning
confidence: 99%